2021
DOI: 10.1108/ijlss-11-2020-0184
|View full text |Cite
|
Sign up to set email alerts
|

Lean waste assessment in a laboratory for training chemical analysts for the pharmaceutical industry

Abstract: Purpose The purpose of this paper is to make a lean assessment of a chemical analyst training laboratory in a higher education institution and identify the main types of waste on a daily basis and understand the lean maturity of the laboratory and establish priority areas of intervention to make the laboratory leanest. Design/methodology/approach A single descriptive case study methodology was used to carry out the lean laboratory evaluation. The lean manufacturing waste terminology was adapted to a lean ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It has been emphasized that the process of creating a lean laboratory differs according to the type and characteristics of the laboratory, although the basic processes used remain the same. Waste in activities is identified; processes are redesigned and improvement activities are conducted to better streamline the workflow and reduce waste (Muiambo et al , 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It has been emphasized that the process of creating a lean laboratory differs according to the type and characteristics of the laboratory, although the basic processes used remain the same. Waste in activities is identified; processes are redesigned and improvement activities are conducted to better streamline the workflow and reduce waste (Muiambo et al , 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As lean evolved as a philosophy, its application became wider. One example of the successful application of lean is in the pharmaceutical industry, especially in the laboratory as presented in the article [28], which showed the success of the use of lean in this area. The authors have found three types of waste; transport, waiting and defects to comprise almost 51.4% of the problem regarding lean assessment of the laboratory.…”
Section: Lean Application In Different Industriesmentioning
confidence: 99%
“…Similarly, Leksic et al [6] mention that, in order to identify which lean tool to use and which one is best suited to the PSC under evaluation, the wastes Taichii Ohno identified should be taken into consideration. The wastes that are covered in this article are the following: defects, which are activities that do not generate value and affect the quality of products, information and/or services; overproduction, defined as excess production that consumes unnecessary time, money, effort, and inventory; extra-processing, which is a process or additional activity for processing unnecessary materials that do not add value to the product or service; waiting, which is the unnecessary idle time of resources and/or workers that the delay and/or availability of resources and information causes; transportation, which refers to equipment, goods, tools, documents or materials transported unnecessarily; inventory, related to the lack of control and accumulation of raw materials, products in process, and finished products; motion, which is the unnecessary movements of workers at workstation and/or plant; and non-utilized talent, which is considered as the underestimation of workers' skills, talents and knowledge to improve the process [7].…”
Section: Introductionmentioning
confidence: 99%